The A to Z of 21stCentury TESOL - Lira Dagalangit Dumaguing (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
As an English Teacher/Trainer for 19 years now, I consider myself lucky to have experienced teaching a range of ESL/EFL/TESOL courses to linguistically and culturally diverse students – those coming from the Philippines, Singapore, Malaysia, Indonesia, People’s Republic of China, Taiwan, Hong Kong, Laos, Thailand, Vietnam, Myanmar, Japan, South Korea, Cambodia, Sri Lanka, India, Solomon Islands, France, Italy, Germany, Russia, Kazakhstan, Uzbekistan, Ukraine, Dubai, Saudi Arabia, Mexico, Switzerland, Eritrea, Colombia, Spain, Holland, and The Netherlands. Given this multiplicity of learner variables, the challenge has always been (at least for me) how to effectively deliver meaningful instruction, ingeniously develop valuable teaching-learning strategies with apposite multimedia use, and fittingly address the varied needs and limitations of my students.Teaching English to Speakers of Other Languages (TESOL) in the 21st century is a mixed blessing seeing that the advancement of technology and the diversity and keenness of students in learning English have prompted teachers to be receptive to both long-established and modern-day teaching methodologies. Gone are the days of sheer chalk talk illustrations and reliance on textbooks for class discussions. Now is the era of multimedia language teaching and the World Wide Web in education. The following is an anthology of my personal observation and experience of what constitutes 21st century TESOL.